Students' views of E-Learning: The impact of technology on learning in higher education in Ireland - SHARP, MARY; O'DONNELL, EILEEN (Information Science Reference (an imprint of IGI Global), 2012)
Students are the end users of the Information Systems that educators use to enhance students? learning experiences. The use of technologies in education has altered the ways in which lecturers and students can interact and has expanded the volume of information that students can access. This study was undertaken to obtain students perspectives on the uses of technologies in higher education to assist educators in improving the pedagogical design of e-learning platforms, known as learning management systems. This chapter provides students? perspectives on the academic use of technologies in two higher education institutions in Ireland. Analysis of the responses received from three hundred and twenty students indicates that students are of the opinion that the use of technologies in higher education can beneficially transform learning; however, technologies will never replace lecturers.
PUBLISHED
Keywords: e-learning